2022
DOI: 10.1029/2022gl100066
|View full text |Cite
|
Sign up to set email alerts
|

Remote Observations of Aeolian Saltation

Abstract: Wind-blown sediment transport can rapidly modify landscapes and produce hazardous conditions in coastal and arid environments (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…This study shows that the median grain size in the measured saltating layer is 75% lower than found at the surface. A recent study by Cohn et al . (2022) showed comparable results.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This study shows that the median grain size in the measured saltating layer is 75% lower than found at the surface. A recent study by Cohn et al . (2022) showed comparable results.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study by showed comparable results. Cohn, Dickhudt, and Brodie (2022) measured grain-size characteris-tics in the field with a holographic system, Sensit sensors, and additional sediment traps and found that grain size decreased from the bed to 42.5 mm above the surface.…”
Section: Discussionmentioning
confidence: 99%